Sprengel anomaly in deletion 22q11.2 (DiGeorge/Velo–Cardio–Facial) syndrome. Issue 3 (21st December 2015) - Radio, Francesca Clementina; Digilio, Maria Cristina; Capolino, Rossella; Dentici, Maria Lisa; Unolt, Marta; Alesi, Viola; Novelli, Antonio; Marino, Bruno; Dallapiccola, Bruno
Abstract : Sprengel anomaly (SA) is a rare skeletal defect characterized by uni‐ or bi‐lateral elevation of the scapula. This anomaly is often isolated, although it can occur in association with other defects, including cervical spine malformations, cleft palate, and facial anomalies. Neural crest migration anomalies have been involved in the etiology of SA. Since the same embryological pathway accounts for some of the clinical features of deletion 22q11.2 syndrome (del22q11.2; DiGeorge/Velo–Cardio–Facial syndrome), we investigated the occurrence of SA in a consecutive series of 235 del22q11.2 patients aged more than 2 years, undergoing a complete clinical and orthopedic assessment of the dorsal and thoracic skeleton. In the present series, two patients were diagnosed with true SA. Present results and published reports suggest that scapular involvement including SA occurs in 1–2% of del22q11.2 individuals. Accordingly, this anomaly should be investigated as one of the possible skeletal findings of del22q11.2 syndrome, while this diagnosis should be excluded in patients presenting with SA associated with other defects. © 2015 Wiley Periodicals, Inc.